The magic of you : a Malory novel - Lindsey, Johanna (Lindsey, Johanna. Malory family series, 1993)
Beautiful, mischievous and shamelessly daring, young Amy is a Malory through and through--as wild and reckless as the most incorrigible of her male cousins. And now that she has reached marriageable age, Amy has set her amorous sights on a most unsuitable mate--the strait-laced American ship captain who once nearly had her Uncle James hung for piracy.